Abnormalities in mitochondrial energy metabolism induced by cryopreservation negatively affect goat sperm motility - Zang, Shengqin; Zou, Shuqi; Chen, Xiangyi; Pan, Bo; Ning, Ao; Qin, Jianpeng; Wei, Yaozong; Du, Kunlin; Ye, Jiangfeng; Liang, Qiuxia; Fang, Yi; Qiongla,; et al. (Frontiers in Veterinary Science, 2025)
The motility of sperm decreases following cryopreservation, which is closely associated with mitochondrial function. However, the alterations in mitochondrial metabolism after sperm freezing in goats remain unclear. This experiment aimed to investigate the impact of ultra-low temperature freezing on goat sperm’s mitochondrial energy metabolism and its potential correlation with sperm motility. The results revealed that goat sperm exhibited mitochondrial vacuolization, reduced matrix density, and significantly decreased levels of high-membrane potential mitochondria and adenosine triphosphate content, accompanied by a substantial increase in reactive oxygen species levels, ultimately leading to a significant decline in sperm viability. Further investigations unveiled that energy-related differential metabolites (capric acid, creatine, and D-glucosamine-6-phosphate) and differential metabolites with antioxidant effects (saikosaponin A, probucol, and cholesterol sulfate) were significantly downregulated. In addition, the activity of key rate-limiting enzymes involved in very long-chain fatty acid biosynthesis and β-oxidation—specifically acetyl-CoA carboxylase, fatty acid synthase, and carnitine palmitoyltransferase I related to capric acid metabolism—was considerably reduced. Furthermore, supplementation of differential metabolite capric acid (500 μM) significantly enhanced the motility of frozen–thawed goat sperm. These findings indicated that the mitochondrial ultrastructure of goat sperm is damaged and energy metabolism becomes abnormal after cryopreservation, potentially affecting sperm viability. The addition of different metabolites such as capric acid to the freezing extender can alleviate the decrease in sperm motility induced by cryopreservation.